2022
DOI: 10.3390/ijerph19127127
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity during Pregnancy and Newborn Body Composition: A Systematic Review

Abstract: The current literature demonstrates that not only is exercise during pregnancy safe, but it has substantial maternal and infant benefits and appears to influence infant growth/size throughout pregnancy and at birth. However, many existing studies have investigated only the effects of prenatal exercise on birth weight. The purpose of this review was to determine the impact or association of maternal physical activity during pregnancy on neonatal body composition assessed between birth and two weeks of age. Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Prenatal exercise has a plethora of benefits for both pregnant women and the fetus(es) they carry. Exercise during pregnancy has been shown to increase the incidence of vaginal delivery as well as lower the incidence of cesarean delivery, excessive gestational weight gain, gestational diabetes, gestational hypertensive disorders, preterm birth, and lower birth weight [1][2][3][4][5][6]. Additionally, prenatal exercise has a positive impact on healthy growth and improved cognition and intelligence of the baby after birth [3].…”
Section: Benefits Of and Recommendations For Exercise During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Prenatal exercise has a plethora of benefits for both pregnant women and the fetus(es) they carry. Exercise during pregnancy has been shown to increase the incidence of vaginal delivery as well as lower the incidence of cesarean delivery, excessive gestational weight gain, gestational diabetes, gestational hypertensive disorders, preterm birth, and lower birth weight [1][2][3][4][5][6]. Additionally, prenatal exercise has a positive impact on healthy growth and improved cognition and intelligence of the baby after birth [3].…”
Section: Benefits Of and Recommendations For Exercise During Pregnancymentioning
confidence: 99%
“…Moderate-intensity exercise training during pregnancy is associated with a lower incidence of gestational diabetes and reduced maternal weight gain [3,6,13,14]. Prenatal physical activity yields the best results in managing gestational diabetes and maternal weight gain when performed in a combination aerobic and resistance training.…”
Section: Prenatal General Medical Conditions and Their Impact On Phys...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, associations between physical activity in pregnancy and birth weight have been inconclusive. For example, a recent systematic review of 32 studies on prenatal physical activity concluded that there is no association between engagement in physical activity throughout pregnancy and newborn body composition markers [ 18 ]. Another study that included objective measures of prenatal physical activity via accelerometry suggested that physical activity was correlated with birth weight, and specifically, that aerobic activity reduced birth weight and increased the number of newborns weighing within the appropriate range [ 19 ].…”
Section: Introductionmentioning
confidence: 99%